2020
DOI: 10.1007/s40615-019-00693-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Health Provider Perspectives Regarding Barriers American Indian/Alaska Native Transgender and Two-Spirit Youth Face Accessing Healthcare

Abstract: Assessing health provider perspectives regarding barriers American Indian/Alaska Native transgender and Two-Spirit youth face accessing healthcare Alessandra AngelinoChair of the Supervisory Committee:Background: American Indian/Alaska Native (AI/AN) youth disproportionately face barriers accessing healthcare when compared to non-AI/AN youth. Additionally, youth who identify as both AI/AN and transgender or Two-Spirit face higher rates of mental health issues and suicidality, along with increased rates of non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 28 publications
0
23
0
1
Order By: Relevance
“…While health care providers working in Native health care settings receive some training in Indigenous culture, many do not receive training in Two Spirit and LGBTQ+ care or the limitations of colonial approaches to gender and sexuality as they relate to Indigenous concepts, including the nuances of Two Spirit identity, which transcends gender identity. 3 Moreover, the participants’ experienced fear associated with gender identity/sexual orientation exposure in the health care system echoes the findings of national surveys from 2015 1 and 2020, 23 reaffirming the need for gender-affirming environments in the health care system, especially when considering the unique health care needs of gender-diverse people. As some participants in our study indicated, their health care providers were unsure and unaware of how to treat and care for them once their gender identity was disclosed.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…While health care providers working in Native health care settings receive some training in Indigenous culture, many do not receive training in Two Spirit and LGBTQ+ care or the limitations of colonial approaches to gender and sexuality as they relate to Indigenous concepts, including the nuances of Two Spirit identity, which transcends gender identity. 3 Moreover, the participants’ experienced fear associated with gender identity/sexual orientation exposure in the health care system echoes the findings of national surveys from 2015 1 and 2020, 23 reaffirming the need for gender-affirming environments in the health care system, especially when considering the unique health care needs of gender-diverse people. As some participants in our study indicated, their health care providers were unsure and unaware of how to treat and care for them once their gender identity was disclosed.…”
Section: Discussionmentioning
confidence: 67%
“…1,2 Furthermore, stigma, discrimination, and lack of gender-affirming care limit the ability of AI/AN people who are transgender and Two Spirit to engage in and benefit from health care settings. 3 Although gender identity and diversity within Native communities was once widely accepted and venerated, the process of colonization often altered the status of Two Spirit people in their communities, forcing assimilation into a Eurocentric culture that rejected such diversity. 4 Today, as a result of such colonization, AI/AN 2SLGBTQ+ people are often associated with health and social disparities, which are likely traceable to barriers to seeking and accessing health care, especially for Two Spirit and transgender people.…”
Section: Smentioning
confidence: 99%
See 1 more Smart Citation
“…ex., Sue et al, 1992;Shin et al, 2016;Rachédi, et Taïbi, 2019;Gouveia et Zanello, 2019), le colonialisme (p. ex., Angelino et al, 2020;Rachédi, et Taïbi, 2019;Nelson, et Wilson, 2018), le sexisme (p. ex., Foster, et May, 2003), le patriarcat (p.…”
Section: Mots Clés : Populations Marginalisées Barrières Systémiques ...unclassified
“…Lesbian, gay, pansexual, bisexual, transgender, gender queer, intersex, and Two-Spirit AI/AN youth experience exponential increases in risk for health disparities. [60][61][62][63] "Two-Spirit" is a unifying term that encompasses both gender identity and traditional Indigenous understandings of identity and is a widely used term in Indigenous communities across North America. In the 2015 US National Transgender Health Survey, AI/AN transgender respondents reported having experienced harassment (86%), physical assault (51%), and sexual assault (21%).…”
Section: Intersections Of Health and Identitymentioning
confidence: 99%